2008
DOI: 10.1371/journal.pone.0003347
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Cerebrospinal Fluid Autoantibodies in Patients with Neuropsychiatric Lupus Erythematosus. Implications for Diagnosis and Pathogenesis

Abstract: BackgroundDespite the uncertainty in the diagnosis of neuropsychiatric involvement in systemic lupus erythematosus (SLE), attempts have been made to record the association of certain antibodies in serum with neuropsychiatric (NP) manifestations. We aimed to assess the behaviour and the association of serum and cerebrospinal fluid (CSF) autoantibodies with NP manifestations in SLE patients (NPSLE).Methodology/Principal FindingsForty-seven SLE patients, hospitalized because of NP manifestations were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 35 publications
(26 reference statements)
3
104
0
4
Order By: Relevance
“…Mice immunized with a multimerized configuration of DWEYS produce antidsDNA/NMDAR antibodies, display glomerular Ig deposition, and exhibit neuronal damage after a breach of the blood-brain barrier (BBB) that allows transit of these antibodies into the CNS (17). In humans, elevated titers of cross-reactive anti-dsDNA/ NMDAR antibodies are present in the serum of 40% of lupus patients and their presence in CSF of lupus patients correlates with CNS manifestations of neuropsychiatric lupus (NPSLE), which afflicts up to 80% of lupus patients (15,(18)(19)(20)(21)(22). Moreover, human anti-dsDNA/NMDAR antibodies have been eluted from postmortem brain tissue, and such antibodies isolated from lupus patient sera can cause brain damage (e.g., cognitive or behavioral dysfunction) in mice (23,24).…”
mentioning
confidence: 99%
“…Mice immunized with a multimerized configuration of DWEYS produce antidsDNA/NMDAR antibodies, display glomerular Ig deposition, and exhibit neuronal damage after a breach of the blood-brain barrier (BBB) that allows transit of these antibodies into the CNS (17). In humans, elevated titers of cross-reactive anti-dsDNA/ NMDAR antibodies are present in the serum of 40% of lupus patients and their presence in CSF of lupus patients correlates with CNS manifestations of neuropsychiatric lupus (NPSLE), which afflicts up to 80% of lupus patients (15,(18)(19)(20)(21)(22). Moreover, human anti-dsDNA/NMDAR antibodies have been eluted from postmortem brain tissue, and such antibodies isolated from lupus patient sera can cause brain damage (e.g., cognitive or behavioral dysfunction) in mice (23,24).…”
mentioning
confidence: 99%
“…Three further publications [57][58][59] were obtained from review of the reference lists of included articles.…”
Section: Literature Search Strategy and Articles Retrievedmentioning
confidence: 99%
“…Three further publications were obtained from review of the reference lists of included articles [57][58][59] . While one of those 59 showed and association between serum anti-NR2…”
Section: Anti-n-methyl-d-aspartate (Nmda) Receptor Antibodiesmentioning
confidence: 99%
“…However, these mechanisms do not account for the majority of symptom complexes associated with NPSLE-in particular, the insidious cognitive decline manifested by up to 80% of lupus patients and the common mood disorders. Recent studies have demonstrated direct neurotoxic effects of lupus autoantibodies; antibodies to n-methyl-D-aspartate receptor (NMDAR), ribosomal P (anti-P), α-tubulin and phospholipid have been shown to bind neurons ex vivo with harmful effects (1)(2)(3)(4)(5) and all have been identified in the cerebrospinal fluid of SLE patients with CNS symptoms attributable to SLE (6)(7)(8)(9). In murine studies, circulating antibrain antibodies can cause neuronal dysfunction and apoptosis after breach of the BBB (5,(10)(11)(12), resulting in functional impairment on cognitive and behavioral tasks, as can antibodies directly injected intraventric- …”
Section: Introductionmentioning
confidence: 99%